The efficiency of players of action-effective football teams in one against one situations - Szwarc, A.; Kromke, K.; Lipinska, P. (Baltic Journal of Health and Physical Activity, 2012)
Background: The aim of this study was to identify and compare the efficiency of action-effective football players in one against one situations (1×1).